Lung cancer screening: Is there a future? - Mary ER O′Brien (Indian Journal of Medical and Paediatric Oncology)
Lung cancer is the leading cause of cancer death worldwide with an average rate of 40-100/100,000 depending on the level of deprivation, and the rates are higher in smokers. The National Lung Screening Trial using three consecutive annual low-dose computed tomography scans is the first and largest screening study to show clear evidence of a significant reduction in lung cancer mortality in selected high-risk subjects. The many on-going European screening studies will generate information on the groups of subjects that may or may not benefit from screening (demographics, pack-years smoked, length of smoking, number of years from quitting etc.) and the required frequency and duration of the intervention. Smoking cessation remains the most important tool for general improvement in health outcomes and in particular lung cancer prevention. Early intervention for investigations of symptoms that are considered mild or common could also change the outcome. Doctors and patients must become increasingly aware that these common symptoms are also potentially symptoms of lung cancer and are not ′normal′ even in smokers.